Factors Associated with Depressive Symptoms Among Community-Dwelling Older People in East-Coast Malaysia - Siti Suhana Zakaria; Siti Nur Illiani Jaafar; Muhammad Kamil Che Hasan; Nik Noor Kaussar Nik Mohd Hatta; Wan Nor Aliza Wan Abdul Rahman (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
Older people are increasing in number globally, and they are likely to have mental health problems, including depression. In this population, the risk of having depressive symptoms is very high due to multidimensional factors, but these symptoms are often undertreated. This study aimed to determine the prevalence and associated factors of depressive symptoms among community-dwelling older people living on the East Coast of Malaysia. A cross-sectional study was conducted in several areas of the state of Terengganu based on multilayered stratified sampling. A total of 240 participants were randomly selected. Several instruments were employed, such as the Geriatric Depression Scale, University of California Los Angeles Loneliness Scale, Pittsburgh Sleep Quality Index, Elderly Cognitive Assessment Questionnaire, Multidimensional Scale of Perceived Social Support, Duke University Religion Index, Barthel Modified Index, and Instrumental Activities of Daily Living Scale. The prevalence of depressive symptoms was 24.6%. The results of the multivariate logistic regression model also revealed that being a single elderly (adjusted odd ratio [aOR] = 4.42; Confidence Interval [CI] = 1.22; 15.96), poor social support (aOR = 3.06; CI = 1.18; 7.93), loneliness (aOR = 21.11; CI = 9.87; 45.18), impaired functional status (aOR = 3.39; CI = 1.22; 9.39), impaired instrumental function (aOR = 6.09; CI = 1.95; 19.0), and having asthma (aOR = 14.14; CI = 2.83; 70.5) were associated with depressive symptoms. Thus, screening older people during primary care is needed for early detection of depression and initiation of community-based interventions to address the psychological aspects of this disorder. Keywords: aging, community dwelling, depression, elderly, factor, mental health Abstrak Faktor-Faktor yang Berkaitan dengan Gejala Depresi pada Kalangan Lansia di Pantai Timur Malaysia. Jumlah penduduk lanjut usia di seluruh dunia semakin meningkat, dan mereka cenderung mempunyai masalah kesehatan mental, termasuk depresi. Pada populasi ini, risiko terjadinya gejala depresi sangat tinggi karena faktor multidimensi, namun gejala tersebut seringkali tidak tertangani. Penelitian ini bertujuan untuk mengetahui prevalensi dan faktor-faktor yang berhubungan dengan gejala depresi di kalangan lansia yang tinggal di Pantai Timur Malaysia. Sebuah studi cross-sectional dilakukan di beberapa wilayah negara bagian Terengganu berdasarkan multilayered stratified sampling. Sebanyak 240 peserta dipilih secara acak. Beberapa instrumen yang digunakan antara lain Geriatric Depression Scale, University of California Los Angeles Loneliness Scale, Pittsburgh Sleep Quality Index, Elderly Cognitive Assessment Questionnaire, Multidimensional Scale of Perceived Social Support, Duke University Religion Index, Barthel Modified Index, dan Instrumental Activities of Daily Living Scale. Prevalensi gejala depresi adalah 24,6%. Hasil multivariate logistic regression model juga mengungkapkan bahwa menjadi lansia tunggal (adjusted odds ratio [aOR] = 4,42; Confidence Interval [CI] = 1,22; 15,96), dukungan sosial yang buruk (aOR = 3,06; CI = 1,18; 7,93), kesepian (aOR = 21,11; CI = 9,87; 45,18), gangguan status fungsional (aOR = 3,39; CI = 1,22; 9,39), gangguan fungsi instrumental (aOR = 6,09; CI = 1,95; 19,0), dan menderita asma (aOR = 14,14; CI = 2,83; 70,5) berhubungan dengan gejala depresi. Oleh karena itu, memeriksa lansia selama perawatan utama diperlukan untuk deteksi awal depresi dan inisiasi intervensi berbasis komunitas yang dapat mengatasi aspek psikologis dari gangguan ini. Kata Kunci: depresi, faktor, kesehatan mental, lansia, penuaan, tempat tinggal komunitas